The role of nutrition in athletic performance: A systematic review of eating behavior and dietary intake patterns - Zsolt Németh; Swamynathan Sanjaykumar (Journal of Applied Movement and Sport Science, 2025)
Background. Nutrition plays a crucial role in optimizing athletic performance, recovery, and overall well-being. Proper dietary intake and eating behavior directly influence an athlete’s energy levels, endurance, and ability to perform at peak capacity.Objectives. This systematic review explores the relationship between eating habits, dietary intake patterns, and athletic performance by analyzing relevant literature.Methods. The study follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, utilizing databases such as Scopus, ScienceDirect, Web of Science (WOS), and PubMed. A total of eight studies were selected based on their relevance to caloric intake, eating behavior, and performance outcomes in athletes.Results. The findings highlight that many athletes fail to meet their caloric needs, often due to poor eating habits and a lack of nutritional knowledge. This deficiency can lead to energy imbalance, impaired recovery, increased injury risk, and reliance on supplements to compensate for inadequate dietary intake. Additionally, restrictive eating patterns and misguided dietary practices contribute to eating disorders and suboptimal athletic performance.Conclusion. This review underscores the importance of nutritional education and structured dietary planning in sports to ensure optimal energy availability, performance sustainability, and long-term athlete health. Implementing personalized nutrition strategies and raising awareness of proper eating habits could significantly enhance athletic performance and well-being.